2021
DOI: 10.3390/ma14133634
|View full text |Cite
|
Sign up to set email alerts
|

Central Composite Design Optimisation in Single Point Incremental Forming of Truncated Cones from Commercially Pure Titanium Grade 2 Sheet Metals

Abstract: Single point incremental forming (SPIF) is an emerging process that is well-known to be suited for fabrication in small series production. The aim of this paper was to determine the optimal input parameters of the process in order to minimise the maximum of both the axial and the in-plane components of the forming force achieved during SPIF and the surface roughness of the internal surface of truncated-cone drawpieces. Grade 2 pure titanium sheets with a thickness of 0.4 mm were used as the test material. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…Moreover, Hirt et al [62] reported that the formability decreases as the tool radius increases. Taking the above-mentioned phenomena the tool radius was determined in preliminary experimental studies which results are published in [17].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Hirt et al [62] reported that the formability decreases as the tool radius increases. Taking the above-mentioned phenomena the tool radius was determined in preliminary experimental studies which results are published in [17].…”
Section: Methodsmentioning
confidence: 99%
“…First of all, the drawpieces show a relatively large springback; incorrectly selected input parameters may result in unsatisfactory roughness of the inner surface of the drawpiece. In areas with small rounding radii, a reduction in the geometric accuracy of the products is observed [17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…QbD is a systematic technique that supports the development of a formulation relying on some independent factors that are investigated for their influence on certain responses to reach the best optimized formula. Several methods for optimization could be utilized, such as central composite designs (CCD) technique [39]. Employing CCD would select the optimized formula by studying certain model graphs, statistical analysis and mathematical equations provided by the system [40].…”
Section: Introductionmentioning
confidence: 99%
“…The aim of their paper was to guide and inspire researchers by identifying current development trends of valuable contributions in the field of Single Point Incremental Forming (SPIF) of lightweight metallic materials. In SPIF, a rotating tool with a rounded tip at its end is used, and the desired shape is formed from clamped sheet metal [ 2 ]. In the literature [ 3 ], a review paper on new advances and future opportunities considered single point incremental to be one of the forming technologies of future-proof materials in aerospace applications.…”
Section: Introductionmentioning
confidence: 99%